Identification of structural variation related to spawn capability of Penaeus vannamei - Yongyu Huang; Hao Wang; Shengyu Xu; Jinli Liu; Qifan Zeng; Jingjie Hu; Zhenmin Bao (BMC Genomics)
Abstract Background The genetic basis underlying spawning abilities in the Pacific white shrimp, Penaeus vannamei, remains largely unexplored. To investigate genetic variations potentially related to reproductive performance, a systematic bioinformatic analysis was conducted to identify structural variations (SVs) with different polymorphic spectra in P. vannamei with high fertility (HF) and low fertility (LF). Results A total of 2,323 and 1,859 SV events were identified exclusively in the HF and LF groups, respectively. These SVs were mapped to 277 genes in the HF group and 231 genes in the LF group. Gene Ontology (GO) enrichment analysis based on SNPs (single nucleotide polymorphism) and SVs revealed several neural-related processes, suggesting the importance of neural regulation in reproduction. Notably, we identified a set of promising genes, including Cttn, Spast, Ppp4c, Spire1, Lhcgr, and Ftz-f1, which may enhance fertility in shrimp. Conclusion In conclusion, this study is the first to establish a link between SVs and reproductive traits in P. vannamei. The promising genes discovered have the potential to serve as crucial markers for enhancing reproductive traits through targeted genotyping.